INVENTARISASI JENIS TUMBUHAN MANGROVE DI AREA TAMAN WISATA BHADRIKA PROVINSI BENGKULU - Dewy Widiawati; Engga Marlinsa; Mardiyati M; Erik Perdana Putra (Jurnal Biosilampari : Jurnal Biologi, 2021)
This study aims to determine the types of mangrove plants in the Bhadrika tourist park, Bengkulu Province. This study uses the method of observation. The data obtained are then immediately taken to the laboratory for identification. The identification process by observing the roots, stems, leaves, flowers and fruit. The mangroves found were, Avicennia alba, Lumnitzera racemosa, Excoecaria agallocha, Aegiceras corniculatum, Bruguiera cylindrical. There were 5 types of mangroves in the Bhadrika Tourism Park which belonged to 5 families.